Farmers' Perception of Among Tani Application - Laiyinah, Fardha Noor; Mumpuni Ningsih, Gumoyo; Ocvanny Amir, Nur (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
The idea of smart city is an innovative well-developed city that uses information and communication technology to help people manage resources and provide information. Within this concept, Batu City Government provides Among Tani application facility for farmers. The application has been running for 3 years and is expected to help and increase farmers' incomes. The purpose of this study was to analyze education, interests, and farming experience with farmers' perceptions in increasing product sales using Among Tani applications and analyze the relationship between farmers' perceptions with the use of Among Tani applications in increasing sales of agricultural products. The time and location of the study were in December 2019 in the Junrejo Village of Batu City. Census sampling technique was used with the number of members of the Bagus farmer group as many as 60 people. The data analysis tool used was Spearman rank analysis and chi-square analysis. The variables used are education (X1), interests (X2), farming experience (X3), farmer perception (Y1) and Usage (Y2). The results of this study are 1) analysis using the Spearman rank shows that there is a relationship between interests and perceptions while there is no relationship between education with farming experience and 2) analysis using chi square shows there is a significant relationship between farmers' perceptions with the use of Among Tani applications in increasing agriculture product sales.